Epidemiological profile of work-related injuries in Lombardy: Insights from Emergency Department data - Cocciolo, Giulia; Gaetti, Giovanni; Ticozzi, Elena Maria; Bodina, Annalisa; Perotti, Gabriele; Stirparo, Giuseppe (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Occupational injuries represent a major public health challenge, impacting workforce productivity and healthcare systems worldwide and Lombardy region, one of the most industrialized area in Europe, is a key region to monitor the phenomenon of work-related injury. Methods: This retrospective observational study analyzed 69,187 work-related injuries reported to Emergency Departments (EDs) across Lombardy, Italy, in 2023. Data were extracted from the Emergency-Urgency Online System (EUOL) and categorized into demographic, temporal, geographic, and clinical variables. Results: Results showed that 69.9% of cases involved male workers, with the highest injury rates among individuals aged 50–55 years (13.4%). Injuries peaked in May and July, with a daily peak at 12:00. Most cases (88.1%) were classified as low severity (green triage). Trauma was the predominant injury type (95.9%), and 91.6% of patients were discharged home. Conclusions: Despite legislative advancements, including Law No. 85/2023, occupational injuries remain a significant issue. Findings highlight the need for enhanced workplace safety measures, targeted interventions for high-risk groups, and improved prevention strategies. Future research should integrate employment data and injury mechanisms to refine risk assessment. Strengthening safety culture and training initiatives is crucial to reducing the burden of occupational injuries in industrialized regions.